Understanding and controlling airborne organic compounds in the indoor environment: mass transfer analysis and applications. (2nd April 2015) - Zhang, Y.; Xiong, J.; Mo, J.; Gong, M.; Cao, J.
Abstract: Mass transfer is key to understanding and controlling indoor airborne organic chemical contaminants (e.g., VVOCs, VOCs, and SVOCs). In this study, we first introduce the fundamentals of mass transfer and then present a series of representative works from the past two decades, focusing on the most recent years. These works cover: (i) predicting and controlling emissions from indoor sources, (ii) determining concentrations of indoor air pollutants, (iii) estimating dermal exposure for some indoor gas‐phase SVOCs, and (iv) optimizing air‐purifying approaches. The mass transfer analysis spans the micro‐, meso‐, and macroscales and includes normal mass transfer modeling, inverse problem solving, and dimensionless analysis. These representative works have reported some novel approaches to mass transfer. Additionally, new dimensionless parameters such as the Little number and the normalized volume of clean air being completely cleaned in a given time period were proposed to better describe the general process characteristics in emissions and control of airborne organic compounds in the indoor environment. Finally, important problems that need further study are presented, reflecting the authors' perspective on the research opportunities in this area.